Sure! Let's break down each step of the equation and provide an explanation for each one.
Given: \( n + (n - 1.5) = 8 \)
Step 1: \( 2n - 1.5 = 8 \)
Rationale: This step combines like terms. The expression \( n + (n - 1.5) \) simplifies to \( 2n - 1.5 \) by adding the \( n \) terms together and subtracting 1.5.
Step 2: \( 2n = 9.5 \)
Rationale: This step adds 1.5 to both sides of the equation to isolate the term with \( n \) on one side. By performing this operation, the equation becomes \( 2n - 1.5 + 1.5 = 8 + 1.5 \), which simplifies to \( 2n = 9.5 \).
Step 3: \( n = 4.75 \)
Rationale: This step divides both sides of the equation by 2 to solve for \( n \). To find the value of \( n \), the equation \( 2n = 9.5 \) is divided by 2, resulting in \( n = \frac{9.5}{2} = 4.75 \).
Summary
- Step 1: Combine like terms.
- Step 2: Isolate the variable term by adding 1.5 to both sides.
- Step 3: Solve for the variable by dividing both sides by 2.